The German elections in the 1870s: why Germany turned from liberalism to protectionism - Sibylle H. Lehmann (Max Planck Institute for Research on Collective Goods, 2009)
In 1878 the liberal parties lost enough votes to loose the majority in the parliament which they had defended in the general election just one year before. In this paper, the question of where the voters came from and why the voting changed so crucially within one year are re-examined. The analysis uses a new set of data aggregated at a lower level than those examined by previous studies and makes use of King's Algorithm, a tool provided by modern political science. The main finding of this paper is that the change towards protectionism was not caused by new, but by floating voters from the agricultural sector.
Keywords: C11; D78; H83; N43; 330